Development of STEM-Based E-Modules on Colloid Material to Train Scientific Literacy Skills - Aria Nanda; Siti Rahmah (UNDIKMA, 2023)
The causes of low literacy in Indonesia are influenced by several factors including teaching materials that are not under the development of students, teacher-centered learning, and low levels of reading ability. This research was conducted to determine the differences in teaching materials used in schools and STEM-based e-modules that were developed and to see the level of feasibility and practicality of STEM-based e-modules. This research used to research and development (R&D) methods by adopting the borg and gall model consisting of over seven stages namely, research and data collection, planning, development, product validation, product revision, field trial, and final product. based on the results of STEM-based e-module validation on colloidal material, the percentage of media and material experts was 89.6% and 90.6%. The practicality of the teacher obtained a percentage of 89%. Based on the validation results of media experts, material experts, and teacher practicality, it was found that STEM-based e-modules were declared feasible and practical to use in the learning process. Based on the results of an analysis of differences in teaching materials in schools and the developed e-modules, it was stated that they were different both in terms of the format and the learning model used.